A Philosophy of Charity and the Debates over the English and Irish Poor Laws in the 1830s. (16th November 2015) - McGauran, John‐Paul; Offer, John
Abstract: The role of charity as a provider of relief was notably little discussed in the comprehensive English Poor Law Report of 1834. By contrast, however, the debate at the time in Ireland over whether any kind of Poor Law at all was desirable ranged much more broadly, with the respective roles of statutory and voluntary provision hotly contested. In fact, beyond the confines of the English Report itself, the topic of the place of charity in relief was exercising plenty of minds on both shores of the Irish Sea. This article examines aspects of the intellectual importance accorded to the role of individual charity and wider voluntary action in welfare provision across the British Isles by some of the central figures in the English and Irish Poor Law debates in the 1830s. It is a study of how justifications were forged to underpin charitable activity and specific policy proposals as advanced by the main proponents of Christian political economy from the late 18th to the early 19th centuries, including William Paley, Thomas Robert Malthus, John Bird Sumner, Edward Copleston, James Ebenezer Bicheno, Thomas Chalmers and Richard Whately. The discussions of Irish circumstances and problems furnish new insights into the substance and reach of a 'philosophy of charity' which was firmly in place by the 1830s.